Trabalho e educação: centralidade e princípio formativo nos Programas de Aprendizagem Profissional - Marina Medrado Correia (2021)
This research sought to understand the ways in which work can be developed as a pedagogical practice within the Professional Learning Program, known as the Young Apprentice Program, specifically the program developed by the Professional Youth Association (Assprom) in the city of Belo Horizonte/MG. For this, we sought to investigate how the formative principle of work is a structuring principle not only of the current education system, but also of non-school educational spheres, from the understanding of work from the perspective of the ontology of the social being. In addition to the literature review, this research is based on in-depth interviews carried out with five employees of the entity in question, through which the internal dynamics of the program, the professionals' conceptions about the program and the challenges to implement it were analyzed, as well as regarding its training potential and the specificities of the labor market for young people. In this sense, recurring notions in discourses and studies regarding technical-professional training were investigated, especially the notions of citizenship and integral training. The conclusions are aimed at recognizing that the way the program is structured, by itself, presupposes work activities as an educational practice, as well as the relationships associated with it and the employment environment. However, it is also recognized that the training potential of the program and the dynamics of employment in adolescence and youth is limited by the proper relations of capitalist sociality, especially with regard to the training role of employers, as normatively determined.